Rivaroxaban versus warfarin for the prevention of post-thrombotic syndrome. Issue 163 (March 2018) - Utne, K.K.; Dahm, A.; Wik, H.S.; Jelsness-Jørgensen, L.P.; Sandset, P.M.; Ghanima, W.
Abstract: Introduction: Despite treatment of acute deep vein thrombosis (DVT) with low molecular weight heparin and warfarin, up to 50% of patients develop post-thrombotic syndrome (PTS). Our aims were to assess whether treatment of DVT with rivaroxaban would reduce the rate of subsequent PTS and improve health-related quality of life (HRQoL) as compared to conventional anticoagulation with low molecular weight heparin (LMWH)/warfarin. Materials and methods: Consecutive patients with an objectively confirmed DVT diagnosed between 2011 and 2014 and treated with either rivaroxaban or warfarin were included in this study 24 (±6) months after DVT. PTS was assessed using the Patient Reported Villalta scale. HRQoL was assessed using the EQ-5D-3L and VEINES-QOL/Sym questionnaires. Results: Total 309 patients were included, 161 (52%) treated with rivaroxaban and 148 (48%) with warfarin. Rivaroxaban-treated patients had a lower rate of PTS (45%: 95% confidence interval [CI] 37 to 52) compared to those treated with warfarin (59%: 95% CI 51 to 66, absolute risk difference 14%: 95% CI 3 to 25, odds ratio (OR) 0.6, P = .01). The adjusted OR for development of PTS was 0.5 (95% CI: 0.3 to 0.8, P = .01) in patients treated with rivaroxaban. HRQoL was significantly better in the rivaroxaban-treated patients. HRQoL measured by EQ-VAS (P = .002) and VEINES-QOL/Sym (P = .005/P = .003) remained significantly better after adjustment. Conclusions: Patients treated with rivaroxaban had lower rate of PTS and better HRQoL after DVT compared to patients treated with warfarin. However, these results should be interpreted with caution due to the limitation imposed by study design. Highlights: Studies have suggested that poor quality of anticoagulation is a risk factor for post-thrombotic syndrome. Direct-acting oral anticoagulants provide rapid and stable anticoagulation from day one. Treatment with rivaroxaban was associated with reduced risk of post-thrombotic syndrome compared to treatment with warfarin Treatment with rivaroxaban was associated with better health-related quality of life compared to treatment with warfarin